The Dichotomy Between Tabarru’ and Mu’âwaḍah Contracts: Perspective of Indonesian Law of Obligation - Aziz, Jamal Abdul; Uswatusolihah, Uus (Al-Manahij: Jurnal Kajian Hukum Islam, 2022)
Among many divisions of contract (‘aqd) in mu’âmalah shar’iyyah, the dichotomy between tabarru’ and mu’âwaḍah contracts is the most influential paradigm in getting to know the jungle of classical and contemporary mu’âmalah contracts. Tabarru’ contract (tabarru’ât) means contracts of virtue as if it should be free from material self-interest or any other profane benefit. Meanwhile, mu’âwaḍah contract (mu’âwaḍât) means business contracts as if it is laden with material calculation and other various forms of self-interest. The dichotomic paradigm of these contracts is quite urgent that it is often made the ground to determine whether or not some material benefit obtained from certain contracts is allowed. It is interesting to observe, that the Indonesian law of obligation which is originating from a Dutch colonial legacy actually also acknowledges such a contract. It is, however, not as strict as its divisions in Islamic fiqh.